2019
DOI: 10.1111/cbdd.13635
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal alkaloids efficient aromatase inhibitors with potential for the treatment of postmenopausal breast cancer

Abstract: Plant‐derived natural products are of great interest due to their diversity in modern drug discovery. Sarcococca saligna has been used for the treatment of different diseases. The present study was aimed at isolating phytochemical constituents including Alkaloid‐C (a), Dictyophlebine (b), Sarcovagine‐D (c) and Saracodine (d) Holaphylline (e) from Sarcococca saligna to investigate the anticancer effect of these compounds. These compounds were evaluated for inhibition of aromatase enzyme of breast cancer in assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Aromatase inhibitors are used to either block the production of estrogen or block the action of estrogen on its receptors and for treatment of estrogen dependant breast cancer. 32,33 In the current study, the investigation of the effect of isolated compounds on aromatase (CYP19A) revealed that all the tested compounds potently inhibited the effect of aromatase enzyme with IC 50 range from 77.41 AE 4.53 to 436.40 AE 25.6 nM (Table 2).…”
Section: Aromatase (Cyp19a) Enzyme Activitymentioning
confidence: 70%
“…Aromatase inhibitors are used to either block the production of estrogen or block the action of estrogen on its receptors and for treatment of estrogen dependant breast cancer. 32,33 In the current study, the investigation of the effect of isolated compounds on aromatase (CYP19A) revealed that all the tested compounds potently inhibited the effect of aromatase enzyme with IC 50 range from 77.41 AE 4.53 to 436.40 AE 25.6 nM (Table 2).…”
Section: Aromatase (Cyp19a) Enzyme Activitymentioning
confidence: 70%
“…The position of the double bond in 7 was assigned by analogy to compound 3 (see above) and by the pattern of lower mass fragments (see fragmentation scheme in Figure S7), which could be rationalized, with difficulty, only if the double bond were in another position than between C-5 and C-6. A large variety of Pachysandra steroids with double bonds in this position have been described (e.g., [14,15,20,21]. Thus, overall, this results in the depicted structure of compound 7.…”
Section: Structural Characterization Of Presumably Active Constituents Based On Their +Esi Qtof Mass Spectramentioning
confidence: 94%
“…Furthermore, all three feature the CF at m/z 283 (C 21 H 31 + ), indicating one further substituent in ring A besides the amide group at C-3. From its [M + H] + ion (C 32 H 49 N 2 O 3 + ) at m/z 509, compound 5 (7.15: 509) suffers a neutral loss of 73 Da (C 3 H 7 NO) which is likely to represent the substituent at C-20 and corresponds to an N-Methylacetamide moiety such as, e.g., present in known compounds such as Epipachysamine A [13] and Saracodine [14]. The fragment at m/z 436 (C 29 H 42 NO 2 + ), resulting from this loss, further loses a molecule of water, leading to the fragment at m/z 418 (C 29 H 40 NO + ); this loss indicates that the single additional substituent is an OH group, either at C-2 or at C-4, leading to the overall structure as depicted.…”
Section: Structural Characterization Of Presumably Active Constituents Based On Their +Esi Qtof Mass Spectramentioning
confidence: 99%
“…Psoralea corylifolia, a plant used in Indian and Chinese traditional medicines, contains a significant amount of bakuchiol, a meroterpene used for its antiandrogenic activity, which shows moderate anti-aromatase activity [85]. Sarcococca saligna, the sweet box or Christmas box, native from Northern Pakistan, contains phytochemical constituents such as alkaloid-C, dictyophlebine, sarcovagine-D and saracodine, which inhibit aromatase [86]. Shu-Gan-Liang-Xue decoction (SGLXD) is a traditional Chinese herbal formula with a potential dual aromatase-sulfatase inhibitor by simultaneously down-regulating the expressions of aromatase and sulfatase in BCa cell cultures [87].…”
Section: Natural Compounds Inhibiting the Steroid Synthesismentioning
confidence: 99%
“…Melatonin [44] Naringin, apigenin, berberine, palmatine, bavachin, jatrorrhizine, bavachinin [80] Alangenes [82] Extracts of Brassaiopsis glomerulata [84] Bakuchiol [85] Extracts of Sarcococca saligna [86] Shu-Gan-Liang-Xue decoction [87,88] Aqueous extracts of white button mushrooms [90] Butein [89] Obacunone [91] 5α-reductase Finasteride [53] Dutasteride [54] Serenoa repens extracts [92] Ethanolic extracts of Epilobium angustifolium [93] (−)-epigallocatechin gallate, biochanin A, daidzein, genistein, kaempferol [94] caffeic acid, grandifloroside [95] polyphenols from Cynomorium songaricum [96] Androgen receptor (SARM) Bicalutamide [65] Enzalutamide [69] Darolutamide [71] Methanolic extract of Brosimum rubescens bark [98] 3,3 -diindolylmethane [99] Androgen receptor (SARD) Darolutamide derivatives [79] Tanshinone IIA [100] Ethanolic extracts from propolis [101] Estrogen receptor (SERM)…”
Section: Pharmacological Targets Synthetic Compounds Natural Compoundsmentioning
confidence: 99%